Correlating Estradiol Levels with Folic Acid and Cobalamin Supplementation: Dynamics of the Rat Oestrus Cycle - Khan Awan, Barkat Ullah; Irfan, Ayesha; Abid, Sara; Bin Nauman, Muaz (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBECTIVE: To examine the effects of supplementary doses of Folate and Cobalamin on the oestrous cycle of female Sprague Dawley rats concerning serum estradiol levels. METHODOLOGY: This experimental study was conducted at the Physiology and Anatomy department's research laboratory at CMH Multan Institute of Medical Sciences, Pakistan. One hundred twenty female Sprague Dawley rats, aged 5-6 months and weighing 150-300g, obtained from the University of Lahore, sampling technique was non-probability convenience sampling. The rats were divided into groups A(Control) and B1, B2, and B3 (Experimental), with thirty rats each. Group A received a daily oral gavage of 2ml/100g of pure distilled water for four weeks. For four weeks, the experimental animals B1, B2, and B3 were given 0.2 mg/kg of Folic Acid, 45µg/kg of Cobalamin, and 0.2 mg/kg of Folic Acid and 45µg/kg of Cobalamin orally via gavage. Every day, vaginal smears were taken. PAP smear slides were prepared. After completion of the study at four weeks, all the animals were euthanized by chloroform inhalation. Blood was obtained to evaluate biochemical parameters using the cardiac puncture method. Serum estradiol levels were measured in pg/ml. Data was analyzed by applying SPSS version 26. RESULTS: The animals in experimental groups B1 and B3 exhibited an atypical oestrus cycle. Following the comparison between groups, a p-value of 0.000 was obtained, which was statistically significant. CONCLUSION: Present research indicates that administering a prolonged supplemental dose of Folic Acid results in an extended oestrous cycle in Sprague Dawley rats, accompanied by elevated serum estradiol levels.